Hubungan Tingkat Berat Jenis Urin dengan Keluhan Kesehatan Akibat Pajanan Panas pada Pekerja Konstruksi Depo LRT - Nafis, Muhammad Syafiq; Ramdhan, Doni Hikmat Hikmat (National Journal of Occupational Health and Safety, 2023)
Background: Construction workers in Indonesia are among vulnerable workers of the negative impact of heat hazard from the work environment. Past research has found that more than 80% of construction workers experienced dehydration and 100% construction workers have experienced heat-related symptoms/illnesses. Objective: The purpose of this study is to analyze the correlation between dehydration (based on urine specific gravity) and heat-related symptoms/illnesses in depo Light-Rail Transit (LRT) construction workers. Methods: This study used a cross-sectional method from secondary data of work environment heat level measurement, workers’ questionnaire, and workers’ urine specific gravity in depo LRT construction 2021. Results : There is a significant correlation between workers’ urine specific gravity level and heat-related symptoms/illnesses on workers. Conclusion: Workers whose urine specific gravity level is not normal (>1,020) or experiencing dehydration, are in more risk of experiencing heat-related symptoms/illnesses compared to workers whose urine specific gravity level is normal (≤1,020) or having a good hydration status.